In situ U–Pb age determination of apatite from carbonatite and kimberlite in the Batain Basin, eastern Oman - Sun, Jing; Jiang, Leiyin; Sun, Jiaxuan (Frontiers in Earth Science, 2023)
Abstract：Northeastern Oman is characterized by carbonatite and kimberlite complex, which are the ideal samples for studying the relationship of carbonatite and kimberlite. However, the ages of Oman kimberlite and carbonatite complex are still unknown, which restrict the understanding of the relationship between carbonatite and kimberlite from Oman. In this study, we use in-situ Laser ablation inductive coupled plasma mass spectrometer (LA-ICPMS) to analyze the apatite from Oman carbonatite, kimberlite and spessartite. The U-Pb apatite ages are 141.6 ± 6.0 Ma, 137.4 ± 5.2 Ma and 141.2 ± 6.2 Ma for carbonatite, spessartite (a kind of calc-alkaline lamprophyre), and kimberlite, respectively. These results suggest that the carbonatite and kimberlite were emplaced contemporaneously, followed by calc-alkaline carbonatite (spessartite) emplaced at Early Cretaceous. The carbonatite, kimberlite and spessartite magmatism of Oman was contemporaneous with the time of Gondwana breakup during the opending of the Indian Ocean. 140-130 Ma is one of the strongest global kimberlite abundance peaks of 250-50 Ma kimberlite bloom, which corresponds with the period of Pangea supercontinent breakup. The Oman kimberlites and carbonatites are related to a distal effect of the breakup of Gondwana portion of Pangea supercontinent, which provided a cool, volatile-fluxed decompression-related circumstance for the formation.